Gambaran Kematian Neonatal Berdasarkan Karakteristik Ibu di Kota Semarang - Sinta Wati; Mateus Sakundarno Adi (Master of Epidemiology, School of Postgraduate Studies, Diponegoro University, Indonesia, 2020)
Background: The Neonatal Mortality Rate of Central Java in 2018 was 7.3 per 1000 live births and the neonatal mortality rate in Semarang City in 2018 was 4.57 per 1000 live births. The purpose of this study was to analyze neoanatal mortality based on maternal characteristics in Semarang City.Methods: This research used descriptive analysis, derived from secondary data in the Semarang City Health Office. The data was taken from Verbal Perinatal Autopsy data sampling from neonatal cases aged 0-28 days who died in Semarang City. In 2019 there were 50 cases out of 101 neonatal death cases.Results: From the analysis showed that neonatal mortality in Semarang City based on the place of delivery were 90% in hospitals with 86% birth attendants assisted by obstetrics and gynecology specialists. Mothers were aged 20-35 years (74%) and 80% have maternal parity less than 3 children, with pregnancy spacing less than 2 years (56%). Beside that, more than 74% mothers have gestational age less than 37 weeks or during the preterm period and 68% of mothers also do Antenatal Care more than 4 times during pregnancy. Most of mothers have hypertension and anemia (20%). Looking at the risk factors, there are 26% of mothers who have a history of abortion, the mother’s age is too old (16%) and childbirth by cesarian section (10%).Conclusion: Neonatal deaths in Semarang City are already numerous in hospitals and delivery assistants by obstetricians. The biggest possibility is that the quality of ANC services is inadequate and not according to ANC-10-T standards.